(untitled) (Sustainability in Debate, 2020)
Public financial aid policies for disaster response actions are a poorly studied topic. This article analyzed information extracted from the databases of the State of Emergency and State of Public Calamity decrees and the costs of disaster relief and response in Brazil, in the period 2013-2017, based on its spatial-temporal distributions. Disaster relief and response costs are also used in a cross-analysis with municipal indicators such as the Human Development Index (HDI) and the per capita Gross Domestic Product (GDP). It was identified that spending exceeded R 800 million. State civil defences accounted for most of the resources used (76.4%). In a universe of 564 municipalities that used financial assistance via the Civil Defense Payment Card, a concentration of 40% of resources was found in 30 municipal civil defences, some of which in municipalities with high HDI and GDP per capita.